Gambaran Kebiasaan Makan Makanan Etnis Minahasa Yang Beresiko Penyakit Jantung Koroner di Lingkungan 5 Kelurahan Paal 2 Kota Manado - Oley, Julia S.; Kandou, Grace D.; Siagian, Iyone E.T.; Ottay, Ronald I.; Rauw-Andries, Lilian; Pandelaki, August J.; Kaunang, Wulan P.J. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2014)
Coroner Heart Diseases (CHD) is one of the main cause of death in many countries, also is the number one cause ofdeath in Indonesia.The high number of CHD in Indonesia goes in line with the high consumption of saturated fattyacid from eating habit. The aim of this research is to picture the eating habit of Minahasa Ethnic, and CHD case atLingkungan 5 Kelurahan Paal 2 Manado. Descriptive research is the method of this research. The population that wasused is all Householders or Housewifes at Lingkungan 5 which are more than 40 years old as much as 355 householders,with 72 householders samples. Result of the research shows 5 kinds of food with the most frequency of beingeaten which are Kangkung Tumis (68,1%), Sayur Pait Ba (25%), Ayam Santan / Kari (20,8%), Brenebon Babi(20,8%), Babi Kecap (19,4), and 5 kinds of food with low frequency of being consumed, which are Paniki (98,6%),Babi Putar (98,6%), Tina’i/Usus Babi (98,6%), Tikus (98,6%), Babi Hutan (98,6%), and 2,8% cases of CHD in Lingkungan5. Conclusion: there were 5 types of frequently consumed food by community in Lingkungan 5 Paal 2 VillageManado City, which were Sayur Kangkung Tumis, Sayur Pait Ba, Ayam Santan/Kari, Brenebon Babi, Babi Kecap, and 5types of rarely consumed food were Paniki, Babi Putar, Tina’i/Usus Babi, Tikus dan Babi Hutan, and history of CHD2.8%, history of CHD in family were 6.9%, history of Diabetes Mellitus 8.3%, and 25% had history of Hypertension,Hyperuricemia, and Dyslipidemia.Keywords: Eating Habits, Coronary Heart Disease